Unraveling the immune system’s role in peripheral nerve regeneration: a pathway to enhanced healing - Zhang, Xu; Zhang, Yanxian; Chen, Yuqing; Ji, Yuxiang; Lyu, Yongmei; Miao, Zengli; Duan, Xuchu; Liu, Xiaoyu (Frontiers in Immunology, 2025)
Peripheral nerve injury (PNI) represents a common challenge in clinical practice. In contrast to the central nervous system (CNS), the peripheral nervous system (PNS) in mature mammals possesses a limited regenerative capacity. Upon the occurrence of PNI, peripheral nerve regeneration (PNR) is initiated, facilitated by the activation of the immune microenvironment and the intrinsic growth potential of neurons. This regenerative process encompasses several key stages, including distal axon degeneration, myelin breakdown, clearance of myelin debris, inflammatory responses from non-neuronal cells, and subsequent axonal regeneration. The immune response, recognized for its role in clearing myelin debris and modulating the local inflammatory milieu, is crucial for initiating axonal regeneration at the proximal stump of nerves. Nevertheless, the precise mechanisms by which the immune response influences PNI and the strategies to harness this process to augment regeneration remain elusive. This article provides a comprehensive overview of the diverse roles and mechanisms of the immune system in PNR and presents insights into potential therapeutic strategies. Furthermore, the article examines immune-associated signaling pathways and their impact on PNR, underscoring the significance of immune modulation in enhancing patient outcomes with PNI. Ultimately, it encapsulates and forecasts the theoretical and practical directions of this field.